Investments as the main factor in the development of Georgian regions - Vashakidze, Natela; Kurdgelia, Natia (Business and Legislation, 2025)
Every region represents a unique economic system. Any option for regional economic policy requires a significant level of investment, which is closely related to solving the problem of institutional development of regions. Innovative scenarios for regional development are unthinkable without the involvement of private business. Accordingly, in modern socio-economic conditions, it would probably be illusory for the region to only expect state support and not take action to overcome a number of problems on its own. Unfortunately, there are few competitive regions in Georgia that could play a driving role in the process of economic growth. This has an extremely negative impact on the qualitative and quantitative indicators of the national economy. The author analyzed statistical information on investments (Foreign direct investment and investment in fixed assets), conducted regression analysis, and established correlations between investments and GDP generated in the region. The analysis revealed significant disparities in the distribution of investments between regions, indicating the need for a more balanced approach to investment infrastructure. The paper uses statistical, comparative, structural, and factor analysis methods.